Surveying the Attitudes and the Preparedness of Healthcare Workers Regarding Communication and Swallowing Difficulties Associated with Long-COVID - Gorman, Amy Kilmurray; Gilheaney, Órla; McTiernan, Kathleen (Trinity Student Medical Journal, 2025)
Introduction: Long-COVID occurs in individuals experiencing symptoms which persist for more than 12 weeks after initial infection. Long-COVID is associated with a collection of symptoms including communication and swallowing difficulties. There is limited peer-reviewed literature available regarding the nature, impact, or management of communication and swallowing difficulties in Long-COVID. Therefore, care delivery may not be optimal, impacting patient outcomes and recovery. The aim of this study was to determine the attitudes and preparedness of healthcare workers regarding communication and swallowing difficulties associated with Long-COVID. Methods: An anonymous online cross-sectional survey was conducted with healthcare workers working with patients living with Long-COVID, with quantitative and qualitative data gathered. Data was collated using Qualtrics and analysed using SPSS and Qualtrics. Results: Overall, 27 professionals completed the survey in full, with sample representation from Speech and Language Therapists (n=15; 55%), Physiotherapists (n=5; 1%), Occupational Therapists (n=4; 15 %), Nurses (n=2; 7%) and Doctors (n=1; 4%); and international representation from the following countries: Ireland (n=15; 56 %), Canada (n= 5; 19%), the USA (n=4; 15%), Australia (n=2; 7%), and the UK (n=1; 4%). Most participants reported that they “sometimes” assess (73%, n=19) and “sometimes” (49%, n=13) or “never” (37%, n=10) provide treatment for communication difficulties associated with Long-COVID. Furthermore, participants reported that they either “sometimes” (44%, n=12) or “never” (30%, n=8) assess for swallowing difficulties associated with Long-COVID and that they either “sometimes” (41%, n=11) or “never” (41%, n=11) provide treatment for swallowing difficulties. Additionally, MDT collaboration was not a constant factor in patient management, with most of the participants reporting that this “sometimes” (63%, n=17) or “never” (7%, n=2) happens. The majority of participants (56%, n=14) had not received specific education or training regarding the provision of appropriate treatment and support for people living with Long-COVID associated communication and swallowing difficulties, with 78% (n=21) of participants indicating that they would like further education in this area. Discussion: This study provided insight into the attitudes and preparedness of MDT members regarding the management of communication and swallowing difficulties experienced by people living with Long-COVID. Although healthcare professionals believe communication and swallowing difficulties are significant issues for people with Long-COVID, they also reported that they do not feel that they are adequately trained in the management of these symptoms to support patients. Participants would welcome further education, further training programmes that focus on communication and swallowing challenges associated with Long-COVID required to support patients in their wellness and recovery journeys.